Hasil dan Dampak Upaya Koersif dalam Penegakan Peraturan Daerah Daerah Istimewa Yogyakarta Nomor 1 Tahun 2014 Tentang Penanganan Gelandangan dan Pengemis - Mutiaratih Larasati Jannati; Johannes Sutoyo (Jurnal Kriminologi Indonesia, 2017)
Control activity is a part of coercive efforts enforcement for Peraturan Daerah Daerah Istimewa Yogyakarta Nomor 1 Tahun 2014 Tentang Gelandangan dan Pengemis, implemented by Satpol PP (Police Unit of Pamong Praja) DIY as a regional unitwho has responsibility and cooperate with Dinas Sosial DIY. In the implementation, the coercive efforts produce Policy Outputs and Policy Outcomes for all levels of society involved in the law. Through the evaluation framework of criminal policy, it is known that the implementation of coercive efforts through enforcement activities in the enforcement Peraturan Daerah Daerah Istimewa Yogyakarta Nomor 1 Tahun 2014 Tentang Gelandangan dan Pengemis have not been in accordance with the desired target. In fact, the raids on Satpol PP are often colored by cases of misinterpretation as a impact of article writing in local regulations related to the criteria of homeless and beggars who have no basis on determining the limits of the intended target. Keyword: Local Regulation, Policy Outcomes, Policy Outputs, Coercive Effort